Distributed fusion cross‐chain model and architecture. Issue 2 (17th March 2022) - Yang, Guozheng; Zang, Cheng; Chen, Jiajun; Guo, Dongsheng; Zhang, Jingzhi
Abstract: Cross‐chain is the key technology to achieve interconnectivity and interoperability across various blockchain networks. It surpasses traditional single‐chain architecture in terms of the performance, capacity, privacy, economic and technical scalability. Cross‐chain can break barriers between institutions, industries, and regions. This paper integrates existing blockchain interoperability technologies and proposes a distributed fusion cross‐chain model in financial industry. In order to support large scale computing and high availability requirements in financial industry, the model is built on a decentralized architecture and highly scalable. It supports large‐scale isomorphic or heterogeneous blockchain cross‐chain data and state interaction. And it achieves reliable financial value circulation in various underlying blockchain networks.